Anthropometric profiling and changes in segmental body composition of professional Football players in relation to age over the training macrocycle - Staskiewicz-Bartecka, W.; Grochowska-Niedworok, E.; Zydek, G.; Grajek, M.; Kiciak, A.; Bialek-Dratwa, A.; Niewiadomska, E.; Kowalski, O.; Kardas, M. (Sports, 2023)
Body composition is an important indicator of the overall health and fitness of team sports athletes, including in football, and therefore, anthropometric profiling of elite football players is useful as part of determining their skills, strengths, and weaknesses to develop effective strength and conditioning programs. One of the tools available to coaches to track correlates of performance and health is routine body composition assessment. The purpose of this study is to describe and compare the body composition and anthropometric profiles of players using the Direct Segmental Multi-Frequency Bio-Electrical Impedance Analysis method, and to manage body composition throughout the round in the 2020-2021 season. The investigation was carried out during the Polish football league, PKO BP Ekstraklasa, spring round of the football season 2020-2021, in which male football players participated. Athletes between the ages of 18 and 25 (n = 16) made up the younger age group, while those between the ages of 26 and 31 (n = 22) made up the older age group. This manuscript is a continuation of the presentation of the results of the study, which was conducted between 7 January and 23 July 2021. At different stages of the macrocycle, participants underwent six different body composition analyses. The younger and older groups of athletes were compared, as well as measurements of time points 1-6. The dominant extremities, assisting extremities, and trunk had larger fat-free mass contents in the older age group. In the study groups, there was a difference in the fat-free mass content between measures 1-6 that was statistically significant. In the younger group, there was a statistically significant difference in the amount of fat mass content between measurements 1-6. In the older age group, no statistically significant changes were found. The study showed changes in fat-free mass and fat mass in body segments; differences were observed between age groups and between different moments of measurement. Age is an important factor in determining body composition and is also related to an athlete`s experience and seniority. Anthropometric profiling and comprehensive body composition analysis are important tools used in preparing athletes for competition.